2018
DOI: 10.1159/000495376
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Wall Stress Induces Phenotypic Switching of Arterial Smooth Muscle Cells in Vascular Remodeling by Activating the YAP/TAZ Signaling Pathway

Abstract: Background/Aims: Increasing wall stress or biomechanical stretch experienced by arteries influences the initiation of atherosclerotic lesions. This initiation is mediated by Yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ), which are both effectors of the Hippo pathway. In this study, the functional roles of YAP/TAZ proteins in the regulation of the stretch-mediated programing of human umbilical arterial smooth muscle cells (HUASMCs) to a proliferative phenotype were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…In the same line, Wang et al observed that YAP/TAZ activation via biomechanical stretching regulates critical aspects of the human umbilical arterial smooth muscle cell (HUASMC) phenotypic switch, as YAP/TAZ knockdown attenuated the stretch-induced proliferative and proinflammatory phenotypes. Moreover, they reported that treatment with atorvastatin suppressed YAP/TAZ expression [42].…”
Section: The Atherosclerotic Processmentioning
confidence: 99%
“…In the same line, Wang et al observed that YAP/TAZ activation via biomechanical stretching regulates critical aspects of the human umbilical arterial smooth muscle cell (HUASMC) phenotypic switch, as YAP/TAZ knockdown attenuated the stretch-induced proliferative and proinflammatory phenotypes. Moreover, they reported that treatment with atorvastatin suppressed YAP/TAZ expression [42].…”
Section: The Atherosclerotic Processmentioning
confidence: 99%
“…When compared to these studies, dronedarone did not show any differential effects on aortic remodeling (decreased aortic media layer and CSA); however, dronedarone also produced changes in the passive mechanical properties of the aorta. Increases in wall stress and biomechanical stretch are a consequence of hypertension and are potent drivers of arterial remodeling [35]. These alterations are also linked to a higher risk of adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological mechanical trauma and changes to cyclic stretch triggers VSMCs to undergo gene, protein expression and phenotypic changes. Examples of this are decreases in contractile genes such as SM22α and those encoding myosin light chain, and increases in cell hypertrophy, proliferation and migration (Huang et al, 1999;Feil et al, 2004;Chiu et al, 2013;Wang et al, 2018). The dysregulated proliferative VSMC phenotype is associated with cardiovascular states where the mechanical environment is perturbed such as pulmonary hypertension and atherosclerosis (Morrell et al, 2009;Bennett et al, 2016).…”
Section: Vascular Smooth Muscle Cells (Vsmcs)mentioning
confidence: 99%